DECLINE CUMULATIVE PRODUCTION ANALYSIS (DCPA) – ALGORITHM, FOR GEOTHERMAL FIELD - Listiana Satiawati; Djoko Sulistyanto; Kris Pudyastuti (Prosiding Seminar Nasional Pakar, 2018)
Forecasting of geothermal production decline is one of the main tasks inreservoir engineering, in order to manage the reservoir and maintain thesustainability of the resource utilization. Studies on the analysis of productiondecline in geothermal fields have been widely implemented, one of which isthe DCPA conducted by H.A. Davila J. (Davila,2017), and applied inKamojang geothermal field - West Java Indonesia. DCPA 'Davila' in Kamojang(steam dominated) geothermal field, appears to be more accurate thanprevious studies. This study is to support the DCPA by creating a computerprogram (algorithm and numeric calculation written in Fortran90/95programming languages (Imam,2009) (Tanja,2005)), thus it